Study on chemical constituents and antioxidant activities of Dianthus caryophyllus L. - Wang, Miaomiao; Shen, Qiuyu; Pang, Jianyu; Mao, Yu; Li, Xiaofei; Tao, Yanxia; Tang, Wenru; Sun, Ruifen; Zhou, Xuhong (Frontiers in Plant Science, 2024)
Abstract: [Objective] Carnation is a plant that holds high value in terms of its edibility, medicinal properties, and ornamental appeal. Creating no sense he aim of this study was to evaluate the antioxidant and antitumor properties of extracts derived from various parts of the carnation plant. Metabolomics technology was employed to identify the primary chemical constituents. [Methods] Initially, we measured the total phenolic and total flavonoid contents in carnation roots, stems, leaves, and flowers, followed by assessing the antioxidant and anti-tumor capabilities of each component using diverse experimental methods. Subsequently, UPLC-MS/MS was employed to identify metabolites in different parts of carnation and investigate their roles in antioxidant and anti-tumor activities. [Results] Mention numerical value- for better underatnding- Results of the study indicated that the methanol extract obtained from carnation flowers and roots exhibited superior antioxidant capacity compared to that from the stems and leaves. This disparity may be attributed to the abundance of polyphenols, flavonoids, and antioxidants present in the flowers, including methyl ferulate and luteolin-4'-O-glucoside. Furthermore, the significant presence of the anthraquinone compound rhein-8-O-glucoside in carnation roots may contribute to their enhanced antioxidant properties. Ten distinct compounds were isolated and recognized in carnation flowers, with Isoorientin 2"-O-rhamnoside and Kurarinone demonstrating notable antioxidant activity and binding affinity to SOD1 and SOD3, as validated through antioxidant screening and molecular docking. [Conclusion] Overall, the findings from this study have expanded our knowledge of the phytochemical composition across different anatomical regions of the carnation plant, providing valuable insights for its holistic utilizati.